The Influence of Job Satisfaction and Organizational Commitment on Employee Performance Mediated by Citizenship Behavior - Salman Farisi (AIBPM Publisher, 2021)
The objectives of this research are to analyze the effect of Job Satisfaction on Performance at PT BAS (Barumun Agro Sentosa), to analyze the effect of commitment to performance at PT BAS (Barumun Agro Sentosa), to analyze the effect of job satisfaction on performance at PT BAS (Barumun Agro Sentosa). Organizational Citizenship at PT BAS (Barumun Agro Sentosa), to analyze the effect of commitment to Organizational Citizenship Behavior at PT BAS (Barumun Agro Sentosa), to analyze the effect of organizational Citizenship Behavior on performance through PT BAS (Barumun Agro Sentosa), to analyze the effect of satisfaction work on performance through mediation of Organizational Citizenship Behavior at PT BAS (Barumun Agro Sentosa), to analyze the effect of commitment to performance through mediation of Organizational Citizenship Behavior at PT BAS (Barumun Agro Sentosa). This study uses an explanatory research approach. The sample in this study was PT BAS (Barumun Agro Sentosa). In this study, researchers used a sampling technique using simple random sampling, amounting to 97 people. Data collection techniques in this study using the interview method (interview), documentation, questionnaires. The data analysis technique in the study used path analysis using the SmartPLs application. From the data, the significant results obtained t the influence of the Job Satisfaction variable (X1) on Organizational Citizenship Behavior (Z) of tcount 3,728> ttable 1,985. This means that the relationship between the two variables is significant. Then the relationship between Job Satisfaction and Organizational Citizenship Behavior (b) has a coefficient value of 0.408 and t statistics value of 3.728> 1.985. This shows a significant relationship. Likewise, the relationship between the Organizational Citizenship Behavior variable on performance (c) has a coefficient value of 0.413 with a t statistics value of 3.385> 1.985 which means significant. Based on the findings above, it can be illustrated as follows, the relationship (c) and (d) is significant, while (a) is also significant, so the Organizational Citizenship Behavior can be a partial mediating variable between Job Satisfaction and Performance. The results of testing the fifth hypothesis show that the variable Organizational Commitment to Performance (a) has a coefficient value of 0.299 with a t statistics value of 2.747> 1.985. This means that the relationship between the two variables is significant. Then the relationship between the variable Organizational Commitment to Organizational Citizenship Behavior (b) has a coefficient value of 0.309 and a value of t statistics of 2.747> 1.985. This shows a significant relationship. Likewise, the relationship between the Organizational Citizenship Behavior variable on financial behavior (c) has a coefficient value of 0.383 with a t statistics value of 3.385> 1.985 which means significant. Based on the findings above, it can be illustrated as follows, the relationship (c) and (d) is significant, while (a) is also significant, so Organizational Citizenship Behavior can be a partial mediating variable between Organizational Commitment to Performance.